Analysis of the Influence of Competency, Work Discipline, and Organizational Culture on Teacher Performance Through the Quality of Graduates as a Moderating Variable - Nasir, Moh.; Supardi; Sriyono (Jurnal Manajemen (Edisi Elektronik), 2024)
Vocational education plays an important role in preparing the younger generation to enter the workforce with skills that are relevant and needed by industry. Vocational High Schools (SMK) have a very important role in preparing the younger generation to enter the workforce with skills that are relevant and needed by industry. Teacher performance in vocational schools is the determining factor in delivering quality education to students. This research aims to analyze the influence of competence, work discipline and organizational culture on performance, by considering the role of graduate quality as a moderating variable. The research method used is a quantitative approach using a questionnaire as a data collection instrument. The research sample consisted of teachers, staff and students from SMK YPM 1 Taman who were selected using purposive sampling. Data were analyzed using multiple regression to test the relationship between competence, work discipline, organizational culture, graduate quality, partnerships, and teacher performance, as well as moderation analysis to test the moderating role of graduate quality. The results of this research can provide valuable insights for policymakers and stakeholders in vocational education in their efforts to improve the quality of graduates and prepare a skilled workforce ready to face industrial challenges